Comparison of the effect of performance level and sex on sprint performance in the biathlon World Cup - Luchsinger, H.; Kocbach, J.; Ettema, G.; Sandbakk, O. (International Journal of Sports Physiology and Performance, 2018)
Biathlon is an Olympic sport combining cross-country skiing with the skating technique and rifle shooting. The sprint (7.5 km for women and 10 km for men) includes two shootings between the three laps of skiing. The aims of the current study are to compare biathletes of different performance-levels and sex on total race time and performance-determining factors of sprint races in the biathlon World Cup. The top 10-performers (G1-10) and results within rank 21-30 (G21-30) in 47 sprint races during the 2011/2012 to 2015/2016 World Cup seasons were compared regarding total race time, course time, shooting time, range time, shooting performance (rate of hits) and penalty time. G21-30 among men and women were on average 3-5% behind G1-10 in total race time, in which course time accounted for 59-65% of the overall performance difference, followed by 31-35% explained by penalty time. The remainder (i.e., 4-6%) was explained by differences in shooting time and range time. The women G1-10 exhibited on average 12% slower speeds than the men G1-10, and course time accounted for 93% of the total time difference of 13% between sexes. The average total hit rates were 92-93% among the G1-10 and 85% among the G21-30 in both sexes. In total, men shot on average 6 seconds faster than women. Course time is the most differentiating factor for overall biathlon performance between performance levels and sex in World Cup races. No sex difference in shooting performance was found.